Design and Simulation of Automated Swaging Machine - Anbazhagan, R; Rekka, G; Rajamanickam, S; Dinesh, C; Ilayaraja, M; Srirangaramanujaa, V (International Journal of Engineering and Technology, 2018)
One of the major time consuming factor on calculating the machine time for the job is loading and unloading. By decreasing the time taken during the loading and unloading of the job, play a significant role in increasing the production of the company. In the proposed study, the swaging machine is automated by means of simple but effective mechanism. The mechanism involves from lifting of the job from its initial position to the top of the slope with the help of slider operated by the pneumatic piston .Then, it is carried to the designated position in the work holding device with the help of controlled gravitational force by belt operated profile. The feeder attached to the swaging machine feed the job and bring back the job, back to the work holding device form there, it is carried to the unloading area by hooks attached belt conveyor. Position sensor is used to sense the position of the job and feed it as an input to operate the other Mechanisms. This work is a cyclic process which converts the swaging machine automated and work continuously. By this proposed work, the production increase, dependency on the reduction of man power, working hours of the swaging machine is increased.